Electrocardiographic profile of rats after malnutritional recovery - Pezolato, Vitor A.; Mascarin, André L.; Paulino, Patrícia C.; Silva, Carlos A. (Medicina (Ribeirao Preto), 2013)
Study Model: Experimental study. Objective: The purpose of this study was to evaluate if the nutritional recovery (NR) restores the metabolic and electrical cardiac changes induced by protein malnutrition. Methods: We used Wistar rats after weaning that were divided into control group (C, 14% diet protein, 90 days), malnourished (M, 6% diet protein, 45 days) and recovered (R, 14% diet protein for 45 days after D). We evaluated the body weight (BW), ECG (heart rate and QRS intervals, QTc and PR) and ventricular glycogen reserves (GLY). The data were submitted to normality tests and Tukey’s test, p <0.05. Results: Group M showed lowers weight than C, and don’t restored with the RN, the event also found in GLY. In ECG, group M showed higher values, indicating cardiac overload, which were restored after nutritional recovery, reaching similar values to C. Conclusion: Changes in cardiac muscle of M animals were reversed with nutritional rehabilitation.